Heterodox Political Economy Specialization and Interconnection -- Concepts of Contradiction, Heterogeneous Agents, Uneven Development - O'Hara, Phillip (Metropolis-Verlag, 2007)
This paper extends the analysis presented by Marc Lavoie in this journal about the relationship between the major schools of heterodox political economy. We argue that the evolution of heterodoxy over the past four decades has seen both specialization and interconnection. The specialization has enabled a degree of detailed analysis of concepts, such as class, demand, innovation, gender, ecology and development. Interconnections between the schools also developed from an early stage. With both forces operating, the specialization promotes clarity of perception and depth of analysis, while the association enables this perception and depth to be linked between the schools. This has led to a degree of crossfertilisation of themes to form broad concepts. Three such broad concepts are examined that are emerging and link aspects of different schools: contradiction, heterogeneous agents, and uneven development. These broad concepts are important for comprehending the social, institutional and historical forces of political economy, and for linking themes from the various schools of heterodoxy.